De nieuwe martelaren: Over zelfmoordterrorisme en religie - Harskamp, Anton van (Tijdschrift voor theologie, 2012)
This article asks how we, who know that Christianity has a tradition of legitimate martyrdom, should today assess suicide terrorists’ claim that they are martyrs for a just cause: how to judge this new ‘predatory martyrdom’ (H. Barlow). After defining suicide terrorism, the article first observes that while at first sight suicide terrorism is a political act, we can also consider it a post-political, highly modern, religious sacrifice, a religious-political ritual performance. The article then invokes the work by American philosopher of religion Ariel Glucklich and others to argue that, within the three monotheistic religions, there is a degree of affinity between physical martyrdom and some mystics’ contemplative martyrdom. Next, the article contends that religious sciences would refine the thought with the idea that there is an essential difference between Christian martyrdom that is said to seek no violence and Islamic martyrdom that, by contrast, does appear to seek violence. Finally, the article lays the groundwork for an assessment of suicide terrorists’ martyrdom by accentuating that predatory martyrdom suspends political morality of any kind. After that, the article uses T.S. Eliot’s Murder in the Cathedral to judge suicide terrorism from a religious perspective to be a religious evil - bad religion - and not only some kind of political injustice.